Regularly alternating poly(amideimide)s containing pendent pentadecyl chains: synthesis and characterization - Sadavarte, Nilakshi V.; Avadhani, C. V.; Naik, Parimal V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
Two new aromatic diamines containing preformed amide linkages, viz., N,N'-(4-pentadecyl-1,3-phenylene)bis(4-aminobenzamide) I and N,N'-(4-pentadecyl-1,3-phenylene)bis(3-aminobenzamide) II, were synthesized by reaction of 4-pentadecylbenzene-1,3-diamine with 4-nitrobenzoylchloride and 3-nitrobenzoylchloride, followed by reduction of the respective dinitro derivatives. A series of new poly(amideimide)s was synthesized by poly-condensation of I and II with four commercially available aromatic dianhydrides, viz., pyromellitic dianhydride (PMDA), 4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA) in N,N-dimethylacetamide (DMAc) employing conventional two step method via poly(amic acid) intermediate followed by thermal imidization. Reference poly(amideimide)s were synthesized by polycondensation of N,N'-(1,3-phenylene)bis(4-aminobenzamide) and N,N'-(1,3-phenylene)bis(3-aminobenzamide) with the same aromatic dianhydrides. Inherent viscosities of poly(amideimide)s containing pendent pentadecyl chains were in the range 0.37-1.23 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C indicating the formation of medium to high molecular weight polymers. The poly(amideimide)s containing pendent pentadecyl chains were found to be soluble in N,N-dimethylacetamide, N,N-dimethylformamide, 1-methyl-2-pyrrolidinone and pyridine and could be cast into transparent, flexible and tough films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-ray diffractograms also displayed sharp reflection in the small angle region (20 approximate to 3 degrees) for poly(amideimide)s containing pentadecyl chains indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition temperatures observed for reference poly(amideimide)s were in the range 331-275 degrees C and those for poly(amideimide)s containing pendent pentadecyl chains were in the range 185-286 degrees C indicating a large drop in T(g), owing to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, were in the range 460-480 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Glass transition temperature; Pendent pentadecyl chain; Poly(amideimide)s; Preformed amide linkage; thermal stability